Self-Care Practices for Common Acute Conditions in the Philippines: A Scoping Review - Loreche, Arianna Maever (Archīum Ateneo, 2023)
Purpose This review aimed to identify and map published studies on self-care practices to manage common acute health conditions in the Philippines. Design/methodology/approach The authors conducted a scoping review in PubMed, Scopus, Cumulative Index of Nursing and Allied Health Literature (CINAHL), ProQuest Central, Journal Storage (JSTOR) and the Philippine Council for Health Research and Development – Health Research and Development Information Network (HERDIN). The authors included all studies on self-care practices to manage common acute conditions, namely low back pain, allergic rhinitis, general acute pain, cough, cold, diarrhea, constipation and stress, published up to 2021 in the Philippines. Information on the article type, aim of the study, study design and setting, population characteristics and size, and self-practices employed for the conditions were extracted and synthesized. Findings The authors identified various self-care practices for acute conditions among the general population and indigenous peoples in the Philippines from 26 studies included in the review: the use of medicines with and without a prescription, appropriate and inappropriate antibiotic use, use of medicinal plants and other traditional and alternative therapies and products, recreational activities and healthy habits and behaviors, and self-management or seeking care from traditional healers (albularyo or manggagamot) or health professionals. A number of considerations influenced their decision on how to manage symptoms, including perceived severity of the condition, availability and perceived effectiveness of treatment, cost, and advice from trusted sources of health information. Research limitations/implications: The authors searched five major databases and a local research database, but some studies may still have been missed in the review. The review also excluded intervention studies on the outcomes of self-care, which limits the authors' ability to make conclusions on the effectiveness of the different modalities of self-care. Social implications: Filipinos engage in a variety of “safe” (or evidence-informed) and “unsafe” (or harmful) self-care practices. While the term “self-care” is not routinely used by the general population and health providers, it is widely enculturated and practiced in the Philippines. Self-care benefits individuals and the health system, but there are also practices that increase risk of adverse outcomes and death including inappropriate antibiotic use, prescription sharing and reuse, and delays in seeking adequate treatment from a health professional. To leverage on self-care in advancing Universal Health Coverage (UHC) goals, the authors recommend a national strategy that provides guidance on how to practice responsible self-care, further research on the effectiveness and safety of alternative medicine and other priority areas, and better integration of self-care in the formal education and health systems. The authors also propose that the research agenda on self-care include acute health conditions, given their impact and burden on health and the economy. Originality/value This is the first published review of self-care practices for managing common acute health conditions, which captured practices of various groups and populations including indigenous peoples.